Analisis Beban Kerja Unit Apron Movement Control Metode Full Time Equivalent Bandar Udara Halim Perdanakusuma - Muhamad Rifqi Auliya’urrahman; Rezty Fauziah Novianty Z; Irfan Abdulhafizh K (Asosiasi Riset Ilmu Pendidikan Indonesia, 2025)
This research is motivated by the high intensity of activity in the apron area, the limited number of personnel, and the implementation of a shift work system in the Apron Movement Control (AMC) unit at Halim Perdanakusuma Airport. These conditions have the potential to cause excessive workloads for personnel, which can impact the effectiveness of operational supervision and disrupt their physical and mental health. The main objective of this study is to analyze the workload of AMC personnel and determine the ideal number of workers to ensure optimal supervision in the apron area. This study uses a quantitative descriptive approach. Data collection techniques were carried out through direct observation and the distribution of questionnaires to all personnel activities in the AMC unit. Data analysis used the Full Time Equivalent (FTE) method to calculate the total actual working time required, and compared it with the standard full-time working hours according to employment regulations. The results showed that the workload of AMC personnel is quite high. Of the seven personnel analyzed, two people obtained an FTE value above 1.28, indicating an overload condition, four people were in the FTE range of 1.00 to 1.28, which is considered normal, and one person had an FTE value below 1.00, indicating an underload condition. These findings indicate an imbalance in the distribution of workload among personnel. As a result, some personnel must perform multiple tasks simultaneously, potentially compromising the quality of oversight and operational safety in the apron area. Based on these findings, a re-evaluation of the division of tasks and workforce within the AMC unit is recommended to create a proportional workload and support optimal safety and operational performance at Halim Perdanakusuma Airport.